(untitled) (Journal of Guidance and Counselling Studies, 2025)
The study examined the influence of small group tutorial on the communication skills among second-year students Kogi State Universities, Nigeria. The study was guided by three research questions and three hypotheses. Descriptive research design was used for the study. A sample of 368 respondents was randomly drawn through the use of multistage sampling technique. The data collected were analyzed using mean and standard deviation to answer the research questions, one way Analysis of variance (ANOVA) was used to test the null hypotheses at 0.05 level of significance. The findings of the study among others revealed that small group tutorial always influenced communication skills of second-year students of Kogi state Universities, Nigeria; that one-on-one tutorial always influence the second-year students` communication skills; that online tutorial often and always influence the second-year students` communication skills; small group tutorial influence the second-year students` communication skills among second-year students of Kogi State Universities. The study concluded that small group tutorial influence the communication skills among second-year students of Kogi State Universities, Nigeria. Based on the findings above, the study recommended that; Institutions should emphasize on interactive and participatory tutorial to achieve more and greater improvements in students’ communication abilities.